Reversed cortical over-activity during movement imagination following neurofeedback treatment for central neuropathic pain. Issue 9 (September 2016) - Hasan, Muhammad Abul; Fraser, Matthew; Conway, Bernard A.; Allan, David B.; Vučković, Aleksandra
Highlights: Long-term neurofeedback treatment reduced central neuropathic pain and cortical overactivity in painful paraplegia. Reduction of event related desynchronization induced by movement imagery was largest in the theta band. This effect was strongest during imagined movements of painful and paralysed legs. Abstract: Objective: One of the brain signatures of the central neuropathic pain (CNP) is the theta band over-activity of wider cortical structures, during imagination of movement. The objective of the study was to investigate whether this over-activity is reversible following the neurofeedback treatment of CNP. Methods: Five paraplegic patients with pain in their legs underwent from twenty to forty neurofeedback sessions that significantly reduced their pain. In order to assess their dynamic cortical activity they were asked to imagine movements of all limbs a week before the first and a week after the last neurofeedback session. Using time–frequency analysis we compared EEG activity during imagination of movement before and after the therapy and further compared it with EEG signals of ten paraplegic patients with no pain and a control group of ten able-bodied people. Results: Neurofeedback treatment resulted in reduced CNP and a wide spread reduction of cortical activity during imagination of movement. The reduction was significant in the alpha and beta band but was largest in the theta band. As a result cortical activity became similar to the activity of other two groups with no pain. Conclusions: Reduction of CNP is accompanied by reduced cortical over-activity during movement imagination. Significance: Understanding causes and consequences mechanism through which CNP affects cortical activity.